ANALISIS KONTRASTIF BAHASA BUGIS DAN BAHASA INDONESIA DALAM BIDANG MORFOLOGI - Andi Fatimah (Universitas Negeri Makassar, 2016)
Abstract: Analysis of Language Konstrastif Bugis and Indonesian in the Field of Morphology. This research is descriptive literature by using a comparative approach. The purpose of research is to describe the distinctive language and Indonesian Bugis in the field of morphology. The results of this study indicate that: (1) Differences in the pattern of morpheme Bugis language and Indonesian contained in: (a) a free morpheme, namely the free morpheme Bugis ends with vowels except e (pepet), while consonants not ending the free morpheme Bugis language except consonant / ng / and / q / (glottal). As for the free morpheme in Indonesian ends with all the vocal and consonant sounds except consonants / q / & / x /, / b / morpheme, ie the use of a prefix and suffix. (2) Differences in the pattern klitikasi Bugis and Indonesian languages are in use proklitik breath and hands. (3) The difference in the pattern of reduplication in language and Indonesian Bugis contained in reduplicated form the majority and reduplication berimbuhan. (4) The difference in the pattern of compounding and Indonesian Bugis language contained in the form of compound words in Bugis who first element consists of a basic word and the second element in the form of words berimbuhan (prefix ma-), while the Bugis language compound words the first and second elements in the form of basic words.